PROTOTIPE APLIKASI PEMASANGAN IKLAN VIA WEB DAN SMS JUALBEBAS.COM UNTUK KAWASAN DENGAN FASILITAS INTERNET TERBATAS - HENDRO PURWOKO (LPPM, 2014)
Indonesia has several web services for free advertisement, paid advertisement, or a combination of both, shortage of the web is there are no facilities such as online advertising advertising via SMS Gateway,enhancement of this facility hopefully can reach out people and the mobile phone owners that are not using the internet. To validate the prototype of the web, the author do some trial experiment of the sale-purchase web named jualbebas.com to the public. hopefully, result of the trial of those web is well work and the SMS facility on the web will facilitate the entrepreneur to develop his business. In this study, the author uses GAMMU as a connecting tools between the modem device with the existing MySQL database on the server (hosting). Creation of the program using the Codeigniter framework with programming language of PHP as its interface and MySQL Database (on the server hosting) which is offline-controlled (Remote). Research results show that the prototype of the advertising online web and SMS facility on those web can facilitate the community in promoting their product. Keyword: SMS Gateway, online advertising, GAMMU, SMS Advertising, sale-purchase web